Analisis Faktor Produksi Kopi Robusta - Andi Aisyah Azzahrah; Kustopo Budiraharjo; Migie Handayani (Hasanuddin University, 2023)
The study aimed to analyze the production factors that influence the production of Robusta coffee and the elasticity of production factors on Robusta coffee production. The research was conducted in Jambu District, Semarang Regency. The survey method was used to select two potential villages, with one farmer group selected for each village as a sample. The data analysis method used was the Cobb-Douglas production function. The results showed that most Robusta coffee farmers were male with an age range of 40-49 years, elementary school education, had been farming for 10-19 years, had 4-6 family members, the average of land area was 0,87 ha, the average of labor was 150,33 HKP/year, the average of manure used was 4.533,33 kg/ha/year, the average of NPK fertilizer used was 391,11 kg/ha/year, and the average number of trees was 1.155,56 sticks with the average of Robusta coffee production was 1.302,71 kg/ha/year. The result of the study showed that simultaneously land area (X1), labor (X2), manure (X3), NPK fertilizer (X4), and number of trees (X5) had a very significant effect on Robusta coffee production and partial manure (X3) and number of trees (X5) had an effect on Robusta coffee production. The elasticity value was 1.142% which was the sum of the elasticity of land area 0,229%, labor 0,016%, manure 0,231%, NPK fertilizer 0,004%, and number of trees 0,662%, which means that Robusta coffee production in Jambu District, Semarang Regency was at the increasing return to scale level.